Desarrollo larval de Cichlasoma nigrofasciatum (Günther), 1868 (Pisces: Cichlidae) en cultivos en laboratorio - Martínez S., Gustavo A.; Murillo S., Róger E. (Revista de Biología Tropical, 1987)
This article describes and illustrates the characteristics in the development of the egg, larvae and juveniles of Cichlasoma nigrofasciatum (Günther), 1868, based on specimens obtained from adults captured in April, 1984 in Embalse de Arenal, Guanacaste, Costa Rica. They were maintained in aquaria, at 23.9±0.5°C; pH: 7.0±0.4; 12:12 hours of photoperiod, with constant aeration and bottom filters. The yolk sac disappears 7 days after eclosion (TL 6.35±0. 27mm). The common number of spines and rays of the anal and dorsal fins for this species appears 24 days after larval eclosion (TL 7.4 ± 1.21 mm). The sequence of fins development is: pectorals, caudal, pelvics, anal and dorsal.